Nonequilibrium inviscid flow about blunt bodies - Lee, R. H.; Chu, S. T.; United States. Air Force. Systems Command. Space Systems Division; Aerospace Corporation (Inglewood, California : Space Systems Division, Air Force Systems Command, United States Air Force, 1964)
An inverse method was used for analyzing the chemically nonequilibrium flow about a blunt body. This method starts with an assumed form of shock shape. The flow field and the thermodynamics behind the shock is determined by a finite difference mesh scheme. The calculation is continued until the sonic point on the body is exceeded. Mass flow rate is integrated along the curvilinear coordinate normal to the shock to determine locations and shapes of the body and the streamlines. The analysis assumes air to be a five-component reacting gas undergoing six coupled reactions with negligible ionization. Complete rate equations including three-body recombinations are used. Numerical examples are given for frozen and nonequilibrium air flows. Three different kinetic models are used for the reacting cases. The results show that even though the pressure and velocities in the shock layer are not sensitive to the air kinetics, the other thermodynamic properties are significantly influenced by the kinetic models chosen. The nitric oxide concentration is greatly enhanced by its direct formation from molecular oxygen and nitrogen. The extra amount of nitric oxide may cause an appreciable increase in gas cap radiation at high altitudes and superorbital velocities. (Author).
"20 January 1964."
Includes bibliographic references (pages 53-54).
Report prepared by Aerospace Corporation, Systems Research and Planning Division, El Segundo, California, for Commander Space Systems Division, United States Air Force, under contract No.
Mode of access: Internet.
Keywords: Space vehicles -- Atmospheric entry; Axial flow; Aerodynamics, Hypersonic